Diurnal variation in exercise responses in angina pectoris. Issue 2 (August 1982) - Joy, M; Pollard, C M; Nunan, T O
Abstract : Thirty caucasian male patients with stable angina were investigated in two groups of nine and one group of 12. Nine normal subjects were also studied. Patients in the first group (on no treatment) underwent symptom-limited exercise electrocardiography at 0800, 1200, and 1600 hours on the same day. Their heart rates and ST segment displacements at 1600 hours were significantly greater than at 0800 hours and the same phenomenon was seen in the second group who had been receiving propranolol 40 mg four times a day. A similar effect was noted for ST segment displacement but not for heart rate in the third group (on no treatment) tested at 0800 hours and 1600 hours on separate days, two to three weeks apart. Normal control subjects showed no diurnal variation in heart rate and their heart rate responses at 1600 hours were reduced by propranolol. The observations show a circadian variation in the ST segment response to exercise in patients with angina and a possible training effect on heart rate with multiple exercise testing on the same day. This variation is associated with a reduction in vagal parasympathetic tone to the heart and should be taken into account in the assessment of patients with angina and in particular when comparing responses to treatment.